2020
DOI: 10.1002/ceas.12173
|View full text |Cite
|
Sign up to set email alerts
|

Supervisor Cultural Humility Predicts Intentional Nondisclosure by Post‐Master's Counselors

Abstract: The authors examined supervisor cultural humility as a predictor of supervisee intentional nondisclosure. Using multiple regression in a sample of 101 post‐master's counselors, the authors found that 20% of supervisees' intentional nondisclosure was explained by their perceptions of their supervisors' level of cultural humility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 20 publications
3
27
0
Order By: Relevance
“…(2019) proposed the multicultural orientation (MCO) perspective as a pragmatic way to enhance cultural understandings about supervisory dynamics, processes, and outcomes through cultural humility, cultural comfort, and cultural opportunities. In addition to recent results (e.g., R. M. Cook et al., 2020; King et al., 2020) and our findings in the current study, researchers may consider conducting further empirical inquiries on MCO. Furthermore, despite being addressed more frequently than the other themes, Focus of Singular Form of Identity and Intersectionality/Multiplicity theme appeared to have limited focus on disability, age, ecology, and intersectionality.…”
Section: Discussionsupporting
confidence: 58%
“…(2019) proposed the multicultural orientation (MCO) perspective as a pragmatic way to enhance cultural understandings about supervisory dynamics, processes, and outcomes through cultural humility, cultural comfort, and cultural opportunities. In addition to recent results (e.g., R. M. Cook et al., 2020; King et al., 2020) and our findings in the current study, researchers may consider conducting further empirical inquiries on MCO. Furthermore, despite being addressed more frequently than the other themes, Focus of Singular Form of Identity and Intersectionality/Multiplicity theme appeared to have limited focus on disability, age, ecology, and intersectionality.…”
Section: Discussionsupporting
confidence: 58%
“…Most participants were drawn from a college/university setting, their mean age being in the 30s in four studies; three studies (Cook et al, 2020;Jadaszewski, 2020;King et al, 2020) had a mean age in the 20s. The majority of participants identified as heterosexual (percentages ranged from 62% to 84%).…”
Section: Setting/samplementioning
confidence: 99%
“…Cook et al. (2020) found that supervisors’ cultural humility may prevent supervisees from intentional nondisclosure in supervision. Similarly, Hutman and Ellis (2019) stated that supervisors’ multicultural competency might also enhance supervisee disclosure.…”
Section: Discussionmentioning
confidence: 99%
“…Besides supervisory working alliance and role ambiguity, there may be other factors supervisors need to pay attention to during the supervision process to promote more supervision-related disclosures from their supervisees. Cook et al (2020) found that supervisors' cultural humility may prevent supervisees from intentional nondisclosure in supervision. Similarly, Hutman and Ellis (2019) stated that supervisors' multicultural competency might also enhance supervisee disclosure.…”
Section: Implications For Future Supervision Researchmentioning
confidence: 99%